Improving Students’ Writing Mastery on Irregular Verbs Through the Dice and Grid Game (A Classroom Action Research in the Eight Grade Students of MTs NU Salatiga in Academic Year 2018/ 2019) - Fitriyanti, Indah Dwi; Sa'adi (Academy of Education Journal, 2024)
The writer conducted the research to improve students’ writing mastery on irregular verbs through the dice and grid game.The research is Qualitatif and Quantitatif research. This research (1) To know the improvement of students’ writing mastery on irregular verbs after using the dice and grid game. (2) To find out how far the dice and grid game improves students’ writing mastery on irregular verbs for the eight grade at MTs NU Salatiga in the Academic year 2018/ 2019. This research method was Classroom Action Research. There was two cycles in the research. Each cycle consists of planing, action, observation and reflection. The result of the research are the students’ mean score was always improve. The students’ mean score of post- test I higher than the students’ mean score of pre- test I. Then the students’ mean score of post- test II higher than the students’mean score of post- test I. The students’ mean score of pre- tes is 37, the students’ mean score of post- test I is 60 and the students’ mean score of post- test II is 61,46. Then the presentage of students’ pre-test score in cycle I is 3.84 %, the presentage of sudents’ post-test score in cycle I is 50%, and the presentage of sudents’ post-test score in cycle II is 57.69%. Based on the result, the dice and grid game improves students’ writing mastery on ireegular verbs. It was from 3,84% up to 57,69%. So more than 55% sudents pass the passing grade.